Do Peso Problems Explain the Returns to the Carry Trade? - Burnside, Craig; Eichenbaum, Martin; Kleshchelski, Isaac; Rebelo, Sergio (Review of Financial Studies, 2011)
[We study the properties of the carry trade, a currency speculation strategy in which an investor borrows low-interest-rate currencies and lends high-interest-rate currencies. This strategy generates payoffs that are on average large and uncorrelated with traditional risk factors. We argue that these payoffs reflect a peso problem. The underlying peso event features high values of the stochastic discount factor rather than very large negative payoffs.]